2013
DOI: 10.1001/jamadermatol.2013.4408
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Survival Disadvantage in Young, Non-Hispanic White Males Compared With Females

Abstract: Male sex is associated with worse survival among white adolescents and young adults with melanoma after controlling for thickness and other prognostic factors. Continued public health efforts are necessary to raise awareness of the outcome of melanoma in young men. Further investigation of possible biological mechanisms that account for these sex differences is merited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
46
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 53 publications
7
46
0
2
Order By: Relevance
“…Most recently, a population-based study by Gamba et al focused on 26,107 individuals from the US National Cancer Institute's Surveillance, Epidemiology, and End Results registry ages 15-39 years. They reported that young men had a 55% decrease in melanoma survival compared with age-matched young women, and concluded that male sex within all specific age groups and across all tumor thickness categories, histologic subtypes, and anatomic sites is associated with a disproportionate burden of melanoma deaths [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, a population-based study by Gamba et al focused on 26,107 individuals from the US National Cancer Institute's Surveillance, Epidemiology, and End Results registry ages 15-39 years. They reported that young men had a 55% decrease in melanoma survival compared with age-matched young women, and concluded that male sex within all specific age groups and across all tumor thickness categories, histologic subtypes, and anatomic sites is associated with a disproportionate burden of melanoma deaths [13].…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences exist in melanoma mortality between men and women. Women present more frequently with earlier stage tumors, experience longer survival and have a better outcome compared with men [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the literature, the progression of melanoma in women shows a slightly better prognosis than in men. Meanwhile, it has also been shown that men have worse disease free and overall survival and gender has an independent predictor of survival in melanoma [14][15][16]. Different hormone levels, UV exposed habits could also play a role in the genderspecific difference [17].…”
Section: Discussionmentioning
confidence: 99%
“…This difference is mainly due to behavioural factors with women diagnosed earlier, resulting in a lower proportion of T3 and T4 CMM compared to men. Biological sex differences may also to some extent contribute to disparities in survival (55,56). The 5-year CMM-specific survival in younger women is now above 95% leaving little room for further large improvements.…”
Section: Discussion Paper Imentioning
confidence: 99%